Camptodactyly: Literature Review and Case Report - Jurgutavičius, Povilas; Minderis, Mindaugas (Lietuvos chirurgija, 2025)
Camptodactyly is a congenital hand deformity characterized by a fixed flexion contracture, most commonly affecting the fifth finger. This literature review and case report highlight the clinical manifestations, and treatment options for camptodactyly. Occurring in approximately 1% of the population, the condition may be unilateral or bilateral and varies widely in severity [1–3]. Camptodactyly often appears at birth or during puberty, linked to genetic mutations, usually sporadic or autosomal dominant in nature [4, 5] painless, non-neurogenic ﬂexion deformity at the proximal interphalangeal joint of the little ﬁnger, which may occur in isolation or in various developmental dysmorphology syndromes. In a ten-year survey of almost 10,000 consecutive neurology outpatient referrals, using a passive case ﬁnding strategy, camptodactyly was observed with a frequency of 0.43%. All were cases of isolated camptodactyly, and all but one were asymptomatic. Camptodactyly was more often bilateral, often asymmetric, than unilateral. A family history was common, sometimes with intrafamilial heterogeneity (symmetry, degree of angulation. Treatment remains controversial, with non-surgical options preferred for mild cases. Surgical intervention is considered when functionality is impaired. In this case, a patient with bilateral fifth finger contractures since birth managed the condition without surgery [3, 6]. This report aims to illustrate current understanding of camptodactyly’s natural course and discusses therapeutic strategies for better clinical outcomes.
Keywords: camptodactyly; congenital hand deformity; genetic mutations; flexion contracture; conservative treatment